TRANSPARENCY AND FINANCIAL PERFORMANCE IN VILLAGE GOVERNANCE: A RATIO-BASED EVALUATION APPROACH - Hikmahwati; Mursidah; Rizky Amelia (ZILLZELL MEDIA PRIMA, 2025)
The enactment of Law Number 6 of 2014 on Villages has granted substantial autonomy to villages in managing governance, including financial and asset management, accompanied by high demands for transparency and accountability. This study aims to evaluate the financial performance of Pulau Sugara Village, Barito Kuala Regency, from 2019 to 2023 using a quantitative descriptive approach. The analysis is based on the Village Budget Realization Reports (LRA), utilizing five financial ratios: expenditure variance, expenditure growth, expenditure harmony (operational and capital), efficiency, and revenue effectiveness. Data were collected through interviews, observations, documentation, and literature studies. The findings indicate that the village's financial performance, in terms of expenditure variance, is categorized as efficient, with an average of 86.08%, indicating that actual spending was consistently below budgeted amounts. However, the expenditure growth rate was relatively low, averaging 13.40%, reflecting slow progress in financial capacity. Efficiency analysis revealed a five-year average of 92.50%, indicating a tendency toward budget inefficiency due to overspending relative to revenue. Despite efficient capital spending and low operational costs, the overall efficiency remains suboptimal. These results highlight the need for better financial planning, enhanced internal audits, and capacity building among village officials to ensure more effective and efficient village financial management.